ANALYSIS OF THE QUALITY OF THE WEBSITE OF THE IMMIGRATION OFFICE CLASS I TPI YOGYAKARTA ON THE SATISFACTION OF ITS USERS WITH THE PIECES METHOD - Gunawan Ari Nursanto; Galuh Boy Hertantyo; R. Yohanes Dhimas Agung (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
Abstract This research aims to find out the quality of the website of TPI Yogyakarta's Class I Immigration Office whether it has been following the standardization of web pages that have been determined by the Ministry of Law and Human Rights through descriptive analysis and further to find out the quality of the website with the PIECES method consisting of performance, information, economy, control, efficiency, and service to website user satisfaction. This research was conducted with a mixed-method approach that convergent parallel design. The first stage of research is carried out with a qualitative approach that is descriptive analysis and the second stage uses a quantitative approach. Qualitative data collection is carried out by observing the appearance of work and the actual state of the website. Quantitative data collection was carried out by distributing questionnaires to 100 respondents. The results of research on website standardization show that four things have not been following the standardization that has been determined. Based on research on the influence of PIECES variables on website user satisfaction, it was found that there were simultaneous influences of PIECES variables and there were three variables that partially affect user satisfaction, namely performance, information, and efficiency, and dominated by efficiency variables.